Phase Composition, Surface Morphology, and Dielectric Properties of Poly(Vinylidene Fluoride)–Cobalt Ferrite Composite Films Depending on Thickness - Pavel A. Vorontsov; Vitalii D. Salnikov; Valerii V. Savin; Stanislav A. Vorontsov; Alexander S. Omelyanchik; Petr V. Shvets; Larissa V. Panina; Petr A. Ershov; Valeria V. Rodionova (Crystals)
This study investigates the effect of polyvinylidene fluoride–CoFe2O4 (PVDF-CFO) composite film thickness on their supramolecular structure, phase composition, and dielectric properties. The composites were synthesized from PVDF with CFO nanoparticles using the Dr. Blade method to obtain film thicknesses ranging from 15 to 58 μm. The data obtained show that the thinner film (15 μm) has a higher β-phase content compared to the thicker films (58 μm), as confirmed by FTIR and Raman spectroscopy. Scanning electron microscopy (SEM) showed that increasing film thickness within the studied range leads to the development of larger spherulitic structures and increased porosity. Atomic force microscopy (AFM) analysis also showed that thicker films have higher tensile strength due to their larger cross-sectional area, while thinner films exhibit lower elasticity. A more uniform microstructure and an increased electroactive phase in thin films result in increased permittivity, which is critical for PVDF-based sensors and energy devices.